INTERLEUKIN-10 REGULATES PD-1-B7-H1-MEDIATED CYTOTOXIC ACTIVITY OF DENDRITIC CELLS - L. V. Sakhno (Scientific Сentre for Family Health and Human Reproduction Problems, 2012)
In this investigation the phenotypic and functional properties of healthy donor and patient with pulmonary tuberculosis (PT) dendritic cells (DCs) were characterized. We also studied the influence of IL-10 on the phenotype and apoptosis-inducing activity of healthy donor DCs. 60 patients with pulmonary tuberculosis with different proliferative response to antigens of M. tuberculosis (purified protein derivative, PPD) and 40 healthy donors were enrolled in this study. It was revealed that DCs, generated in vitro from PT patient's blood monocytes with GM-CSF+IFN-α, were characterized by increased B7-H1 expression, up-production of IL-10 and reducing of allostimulatory activity in mixed lymphocyte culture (MLC). The endogenous IL-10 production by DCs was correlated with expression of B7-H1 in the general group of persons. It was revealed that addition of IL-10 to semi-mature DCs of healthy donor results in increasing of B7-H1 expression, diminishing of allostimulatory activity and enlargement of pro-apoptogenic activity of DCs.